AN ANALYSIS OF GRAMMATICAL COHESION IN STUDENTS’ WRITING (A Case Study in the Eleventh Year Students of SMAN 1 Garut) - Zulfan Nurohmah Maulida; Surtiana Harjadijaya; Irsyad Nugraha (Institut Pendidikan Indonesia Garut, 2020)
This study focused on AN ANALYSIS OF GRAMMATICAL COHESION IN STUDENTS’ WRITING. It aims to discover what kinds of grammatical cohesive devices used in students’ writing recount text and how these grammatical cohesive devices are used in the students’ writing recount text. To achieve the aims of this research, the researcher used qualitative as research method and case study design. The data source of this research is the eleventh grade students of SMAN 1 Garut that consist of 10 students as participant. The writer has chosen 3 students from high-achiever, 4 students from middle achiever, and 3 students from lower-achiever. For collecting data, the writer used writing test. The writer put the data based on kinds of grammatical cohesion. The writer identified and classified each sentence in data, and the writer analyzed them by using theory from Halliday and Hasan (1976), Halliday&Mathiessen (2004), Bloor & Bloor (2004), Eggins (2004). The result of this study showed that all type of grammatical cohesion appeared in students’ recount text, but the use of substitution and ellipsis were rarely used by students in writing recount text while the use of reference and substitution were often used in students’ writing